Optimal parabolic arches - Leitman, M.J.; Villaggio, P. (International journal of engineering science, 2010)
An explicit solution for the elastic stress state in a thick parabolic arch subject only to symmetric loading at its foundations is presented. This solution is found using the complex variable method of plane elasticity. The proposed stress solution has the interesting property of being isoresistent in the sense that exterior and interior boundaries of the arch convey constant hoop stresses of equal but opposite sign. Moreover, all hoop stresses are constant.